ChemInform Abstract: Pd(0)‐Catalyzed Carboiodination: Early Developments and Recent Advances. Issue 18 (May 2015) - Petrone, David A.; Le, Christine M.; Newman, Stephen G.; Lautens, Mark
Abstract Review: 172 refs.